Legal Analysis of the Implementation of Wills that are Detrimental to Heirs According to the Civil Code - Hj. Mahanum Z (Outline Publisher, 2025)
This study examines the implementation of a will that causes losses to heirs according to the Civil Code (KUHPerdata). The main problems include: (1) legal limitations on implementing a will when it reduces the heirs' absolute rights (legitieme portie); and (2) the position and responsibilities of the executor (executeur testamentair) and the validity implications of a will deed unknown to the heirs. The study uses a normative legal approach, examining key Civil Code provisions (such as Articles 874, 913, 1005, and 1016) supported by secondary legal materials like doctrines and jurisprudence. The results indicate that a will's implementation is limited by the principle of protecting the legitieme portie. Any grant exceeding this limit can be subject to a reduction (inkorting) request by entitled heirs. The executor of a will has the authority to manage and ensure the testator's wishes are fulfilled but can be dismissed for negligence, acting beyond authority, or causing harm. Furthermore, a will is legally binding if it meets formal and material requirements, even if not yet known to the heirs. The heirs' ignorance does not automatically negate the deed's validity but opens legal remedies, such as incorting or cancellation, if it is proven to conflict with applicable legal provisions. The conclusion emphasizes the importance of complying with legitieme portie limits and ensuring the executor's accountability to prevent harm. It also highlights the notary's active role in overseeing formalities and notification to guarantee certainty and fairness in the will's execution.